Freedom of Expression in the US Constitution: Formation and Development - O. V. Sendetskaya (Law and Safety)
The essence of such rights as the right to freedom of expression and the right to freedom of speech has been analyzed. Based on the United States regulations, the author has compared approaches to understanding and interpreting freedom of speech and freedom of expression.